2018
DOI: 10.1186/s13039-018-0386-0
|View full text |Cite
|
Sign up to set email alerts
|

Submicroscopic chromosomal imbalances contribute to early abortion

Abstract: BackgroundChromosomal abnormalities are one of the genetic mechanisms associated with abortion. However, the roles of submicroscopic chromosomal imbalances in early abortion are still unclear. This study aims to find out whether submicroscopic chromosomal imbalances contribute to early abortion.MethodsA total of 78 chorionic villus specimens from early spontaneous abortion patients with no obvious abnormality are collected after miccroassay analysis (the case group). At the same time, 60 chorionic villus speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Several studies have found that numerical chromosomal abnormalities on chromosomes 1 and 19 were associated with some diseases and miscarriage. [46][47][48] The incidence of chromosomal abnormalities and numerical chromosomal abnormalities increased with an increasing age of the pregnant women, with the lowest incidence being in individuals < 30 years old. This result is in line with a previous study.…”
Section: Comparison Of Cnv Results Of Fetuses According To Different Age Of Pregnant Women and Gestational Weekmentioning
confidence: 99%
“…Several studies have found that numerical chromosomal abnormalities on chromosomes 1 and 19 were associated with some diseases and miscarriage. [46][47][48] The incidence of chromosomal abnormalities and numerical chromosomal abnormalities increased with an increasing age of the pregnant women, with the lowest incidence being in individuals < 30 years old. This result is in line with a previous study.…”
Section: Comparison Of Cnv Results Of Fetuses According To Different Age Of Pregnant Women and Gestational Weekmentioning
confidence: 99%
“…We also found that no abnormal chromosome number was detected in Chr1, Chr17, and Chr19, which might result from the insufficient sample size. The incidence of miscarriages caused by T1, T17, and T19 was relatively low, although several studies found numerical abnormalities of Chr1 and Chr19 in abortion tissues [ 25 , 26 ]. There were 21 mosaicisms detected in this study, and three were low-level mosaicism: 47,XNN[15%]/46,XN[85%]; 45,X[10%]/46,XN[90%]; 47,XN, + 4[10%]/46,XN[90%].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that submicroscopic CNVs could be one of genetic causes in pregnancy losses [1419]. In this study, 23 CNVs were identified in 326 POC samples using SNP-array, of which 11 CNVs were interpreted as pathogenic for these CNVs were cytogenetically visible alterations (>3-5 Mb) without well-established cytogenetic heteromorphisms, and 7 CNVs were classified as VOUS because whether these CNVs cause spontaneous abortions is still an open question (Table 1).…”
Section: Discussionmentioning
confidence: 99%